PENERAPAN MODEL META-UTAUT (UNIFIED THEORY OF ACCEPTANCE AND USE OF TECHNOLOGY) UNTUK MEMAHAMI PENERIMAAN DAN PENGGUNAAN MODUL E-LEARNING KOMPETENSI TEKNOLOGI INFORMASI PADA MAHASISWA UNIVERSITAS BRAWIJAYA - Wicaksono, Agung (Jurnal Administrasi Publik, 2023)
The Use of meta-UTAUT (Unified Theory of Acceptance and Use of Technology) Model to Understand the Acceptance and Use of Information Technology Competency E-Learning Modules in Brawijaya University Students. One of the uses of e-learning in Brawijaya University is in information technology (IT) certification for students. To prepare the certification exam, they can study online e-learning modules. This research aims to understand the acceptance and use of e-learning modules of IT certification among students. This study used quantitative descriptive methods and meta-UTAUT model. Data collection was done using a stratified random sampling approach with 3479 respondents. Data analysis used Structural Equation Modeling (SEM) method and Partial Least Squares (PLS) with WarpPLS 8.0. The study results indicated that performance expectancy, effort expectancy, and social influence have a positive effect on attitude and behavioral intention. Facilitating conditions, perceived information security, and compatibility influence attitudes. Resistance to change, perceived enjoyment, and perceived social pressure influence behavioral intention. However, facilitating conditions, personal innovativeness in IT, and compatibility have no effect on behavioral intention. In addition, perceived social pressure has no effect on attitude.